THE CAUSES, SYMPTOMS, PREVENTION, AND TREATMENT OF THIS AILMENT IN CHILDREN - Vahobova Maftuna Bahodirovna (TADQIQOTLAR, 2026)
Abstact: In pediatric populations across the globe, congenital full left-sided cleft of the palate, alveolar process, and upper lip continues to be a major health concern. Improving therapeutic outcomes requires an understanding of its existing epidemiological patterns and causative causes. Reviewing the epidemiology, aetiology, preventative measures, and available treatment options for infants with congenital full left-sided clefts of the upper lip, alveolar process, and palate is the goal of this research. To find important trends in illness prevalence and treatment effectiveness, a thorough review of current clinical data and literature was carried out. The occurrence in children aged is shown by the epidemiology. A complicated interaction of environmental cues is one of the aetiological elements. The major focus of prevention is still [discuss basic prevention, such as immunization]. With the advent of [name important therapy, such as focused multidisciplinary care, which dramatically lowers death rates], treatment has changed. Although the prognosis for infants with congenital full left-sided cleft of the upper lip, alveolar process, and palate has improved due to medical improvements, early detection and effective preventive initiatives are crucial to lowering the disease’s worldwide impact.